PENGARUH PLATFORM ONLINE FOOD DELIVERY (OFD) TERHADAP PERILAKU KONSUMTIF MAHASISWA - Ahmad Fauzan; Ricky Firmansyah; Adinda Shafa Qolbu Risnanti (JURNAL EKONOMI PERJUANGAN, 2023)
Online Food Delivery is a food delivery service carried out by an application that serves online ordering, the use of online food delivery is very popular among Indonesian people such as students or university students. This research is a study conducted to find out "the influence of a consumptive lifestyle and Online Food Delivery. The method used in this study is a quantitative method using Google form. We conducted research on Digital Technology University students with a research sample of 39 respondents from semester III - V semester students of the Digital Technology University management study program aged between 20-23 years. The technique in collecting data uses a questionnaire technique which contains questions about the Online Food Delivery platform then the results of the information are analyzed using a descriptive qualitative method. The results of the research show that there is a significant correlation and influence between Online Food Delivery on consumptive behavior actually 46.2% meaning that Online Food Delivery has an effect positive and significant impact on consumptive behavior among students in using the Online Food Delivery platform, besides that consumptive behavior of students is shown to female students which cannot be avoided without awareness to be wise in using the Online Food Delivery platform. Furthermore, the average student does Online Food Delivery because it is practical, there are lots of promos and invitations from friends to buy food that is currently viral. Keywords: Consumptive Behavior, Food, Platform, Students ,Technology